PERAN PROGRAM DIRECTOR TV DALAM PROSES PRODUKSI VISUAL PROGRAM ACARA SEMESTA BERTILAWAH DI MNC TV - agung raharjo; anisti ans (Jurnal Komunikasi, 2018)
In order to produce a qualified televison program, there are several things that must be concerned, one of them is the crucial role of Director of television programs. Director of television programs is a person whom put in charge technically on the implementation of production at one television  program. Other than that, the Director of television programs controls the production that he/she is dealing with, coordinating with all elements, facilities, and the team members during the rehearsal.  Director of television programs helps and gives the crucial instructions and the details to all crew members either in the studios or locations, including the production team.In this essay the writer is using descriptive-qualitative method which explains the events. The study itself is  purposed to describe or to explain the ongoing events on the research regardless the previous events & afterwards. The role of Director of television programs in a production program is very important to comprehend and master the planning and the the visual controls on the Program Semesta Bertilawah di MNC TV. Not only mastering one subject but also insisted him / her to be able to build a good communication and can be cooperative with the relevant agencies. Keyword : Program Director, Production, Visual